2021
DOI: 10.1177/13694332211020406
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of concrete composite slabs with truss type shear connectors of different orientation angle

Abstract: Concrete composite slab system with pre-cast bottom segment and cast-in-situ top segment is gaining importance due to wide-ranging applications in buildings, bridges and industrial flooring, etc. These slabs may also be subjected to repeated loading during its service life and hence, it is essential to evaluate their static and fatigue behaviour under flexural loading. In present study, at first, experimental investigations are conducted to evaluate the performance of composite slabs with truss type shear conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, the cost of formwork can be minimized. Deng et al [9] synthesized other investigations [8,[10][11][12][13] and showed that the precast RC composite slab with inclined steel truss bars acquires beneficial features of both precast and RC slabs cast in situ, containing high construction efficiency and cost savings, high integrity, high reliability, and comparable mechanical behavior to that of popular slabs cast in situ. These studies also pointed out that the inclined steel truss bars have an insignificant impact on the load-carrying capacity but can greatly improve the ductility of the RC composite slab.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the cost of formwork can be minimized. Deng et al [9] synthesized other investigations [8,[10][11][12][13] and showed that the precast RC composite slab with inclined steel truss bars acquires beneficial features of both precast and RC slabs cast in situ, containing high construction efficiency and cost savings, high integrity, high reliability, and comparable mechanical behavior to that of popular slabs cast in situ. These studies also pointed out that the inclined steel truss bars have an insignificant impact on the load-carrying capacity but can greatly improve the ductility of the RC composite slab.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also pointed out that the inclined steel truss bars have an insignificant impact on the load-carrying capacity but can greatly improve the ductility of the RC composite slab. The influences of different steel truss bars and innovative joint configurations on the flexural bending tests of composite slabs have been examined [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The shear keys can also be connected to temporary I-beams to increase the stiffness of the PBSs to realise support-free construction (Figure 2b). There are large bodies of systematic research on each [3][4][5][6][7][8][9][10][11]. Liu et al [12] confirmed the practicality of using STLSs by empirical testing; Ma et al [13] investigated its mechanical properties in construction and in service by testing and numerical modelling; Zhao et al [14] analysed the influence of parameters, such as concrete strength and truss height and diameter, on the mechanical properties of STLSs using ANSYS software; and Cheng [15] developed a short-term stiffness model for STLSs from theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%